One day seminar on decommissioning programme of the Windscale AGR Wednesday 17 February 1999 at the Institution of Civil Engineers, Great George Street, Westminster, London SW1P 3AA (British Nuclear Energy Society, 1999)
Proceedings of a seminar held on 17 February 1999.